Rancang Bangun Cetakan Botol Ukuran 30 ml Model Blow Pada Mesin Injection Molding - Siagian, Martua Sangap; Ramdan, Dadan; Umroh, Bobby (Universitas Medan Area, 2023)
At present, the need to use plastics and the advancement of manufacturing technology for the material itself drive people's demand for plastics, and the development of technology has further increased competition in all fields of industry. Therefore, the plastics industry needs to increase production in terms of quality and quantity. In this way, plastic can slowly replace iron and steel due to its good moldability and light weight. In this research, as a research method, we use quantitative methods by conducting surveys, data collection and field research related to the research theme. After the data is collected, the next step is the fabrication of the test equipment. From the mold fabrication results, the mold is in the shape of a 30 ml bottle with dimensions of 105 mm x 40 mm, inlet ø 6 mm, outlet 3 mm, and the mold is made of aluminum. This mold is called the 3 plate system and the mold consists of 3 main parts which are divided into 3 parts. Good and ideal molding results were obtained with HDPE (High Density Polyethylene) material with injection speed parameters of 8 rpm and temperature of 190°C.